Universal Moral Values In Arabic Language Structure: A Concept, Component And Meaning - Mohd Nizwan Musling; Muhammad Zahid Ismail; Mohd Rosmizi Abd Rahman; Robiatul Adawiyah Mohd @ Amat (Human Resource Management Academic Research Society, 2024)
Indexed by ERA